IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH CONTEXT CLUES STRATEGY - ENY DWI MARCELA; DESTIA HERLISYA; PURNA WIRATNO (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2024)
This study aims to enhance students' reading comprehension through the use of context clues. This research focused on first semester English Education major students at STKIP PGRI Bandar Lampung. It comprised of 20 students. This study employed Classroom Action Research (CAR) in two cycles. The researchers collected data using both tests and non-tests. This study employed both formative and summative tests. During non-testing, researchers used observation sheets and field notes. The researchers analysed the data using both quantitative and qualitative methods. The study found that using context clues effectively improves students' learning and reading comprehension. In cycle 1, 8 students passed the exam with a percentage of 40%, while 12 students failed with a percentage of 60%. It improves in cycle two, with 16 students passing (80%) and 4 failing (16%). It may be concluded that using the context clues approach delivers positive learning effects. The mean score of total score in cycle 1 was 6.34 while in cycle 2 the mean score was 7.68. The improvement of students’ learning activity from cycle 1 to cycle 2 was 0.58. The context clues strategy successfully improved the learning activity and reading comprehension of first semester English education students at STKIP PGRI Bandar Lampung in 2023/2024.